OHP-017 Ability of infusion devices to deliver the expected volume of antineoplastic drug in solution: an in vitro assessment. (24th March 2015) - Lebecque, M; Simon, N; Legrand, JF; Pinturaud, M; Vasseur, M; Barthélémy, C; Décaudin, B; Odou, P
Abstract : Background: For several years, many infusion systems have been marketed for the administration of antineoplastic drugs (AD). Purpose: To compare the ability of these devices to deliver the expected volume of antineoplastic drug in solution. Material and methods: Seven infusion devices were assessed (see table 1 ) by simulated infusions with a radiotracer ( 99m TcO4 − ) as drug substitute. The same activity (370 MBq) was diluted in 250 mL 0.9% NaCl bags. The evolution of the drug concentration at the egress of the infusion system was recorded continuously with a sodium iodine crystal detector. The area-under-curve of drug concentration according to time of both administration (AUCadm ) and rinsing (AUCrin ) steps were calculated using the linear trapezoidal rule after correcting for radioactivity decay. The rinsing volumes (Vrin ), volumes required to get no more radioactivity, were measured in a graduated test tube. The values were compared using a Kruskall-Wallis test (p < 0.05). Results: Despite the differences in dead-space volume, AUCadm were not significantly different (see table 1 ). The rinsing volumes were significantly different between the tested devices, ranging between 46.8 ± 5.7 mL and 92.2 ± 8.9 mL. Conclusion: The rinsing conditions required to administer the same dose are really different between devices. The impact of good handling practice of these devices has to be assessed on the pharmacokinetic parameters. Reference: Kontny NE, Boos J, Würthwein G, et al . Minimization of the preanalytical error in pharmacokinetic analyses and therapeutic drug monitoring: focus on IV drug administration. Ther Drug Monit 2012;34:460–6 No conflict of interest.